Mental health of Indonesian millennials: A descriptive analysis of depression severity - Rinaldi, Martaria Rizky; Sari, Kadek Indah Purnama; Malika, Ni Made Devina Candra (Psychological Research and Intervention, 2026)
Depression among young adults has become an increasing global public health concern, with substantial personal and societal impacts. While several studies have explored depression in younger populations, research specifically targeting millennials in Indonesia remains limited. This study aimed to describe the severity of depression and examine gender differences in depression levels among Indonesian millennials. A quantitative, descriptive-comparative design was employed. The participants consisted of 200 individuals aged 26 to 40 years, representing the millennial generation, who were recruited through purposive sampling. Depression severity was measured using the Patient Health Questionnaire-9 (PHQ-9), a validated self-report instrument. Data were collected through an online survey and analyzed using descriptive statistics and Independent Samples t-Test (with Mann-Whitney U as an alternative when assumptions were not met). The findings revealed that approximately 29% of respondents experienced moderate to severe levels of depression, indicating a substantial mental health burden within this demographic. No significant differences in depression scores were found between male and female respondents. These results highlight the urgency of addressing mental health needs among Indonesian millennials, who are currently in a critical phase of socio-economic productivity and family formation. It is essential to strengthen early detection and develop tailored mental health interventions that are accessible and culturally relevant for this population. Future research should consider longitudinal designs to explore protective and risk factors for depression, and the potential of digital-based mental health interventions to support this tech-savvy generation.